Cure Characteristic, Tensile and Morphological Properties of Graphene Nanoplatelets (GNPs) Filled NR/EPDM Composites - Yaakub , Juliana; Mohamad, Noraiham; ABD RAZAK , JEEFFERIE; Jano, Zanariah; Shueb, Mohamad Iqbal (AENSI, 2014)
Proper filler-matrix compatibility is a key factor in obtaining nanocomposites with well-dispersed nanofillers displaying enhanced properties. Natural rubber/ethylene–propylene–diene rubber (NR/EPDM) blends reinforced with untreated and treated graphene nanoplatelets (GNPs) were prepared through melt compounding. The untreated and treated GNPs were varied from 0, 0.25, 0.50, 1, 3 and 5 wt% into the compounding recipes to determine the influences of filler loading to the cure characteristics, swelling and morphological properties of the nanocomposites. It was observed that the scorch time (Ts2), cure time (T90), minimum (ML) and maximum torque (MH) increased as untreated and treated GNPs filled in NR/EPDM composites increased. However, ML and MH values of treated GNPs filled NR/EPDM composites exhibit decreased as compared to untreated GNPs filled NR/EPDM composites. These findings were further supported by swell behavior and morphological characterization of the nanocomposites.